A 50‐Ω microstrip line fed shorted equilateral triangular microstrip antenna. Issue 5 (8th April 2018) - Singh, Bharati; Sarwade, Nisha; Ray, K. P.
Abstract: For the fundamental TM10 mode of an equilateral triangular microstrip antenna (ETMSA), along its height, the impedance value is maximum at the vertex, zero at the isocenter and finite value at the base. Along the base, the impedance remains constant in between 150 to 200 Ω, depending upon the design. Thus, 50‐Ω microstrip (MS) line cannot be used to directly feed an ETMSA at its base. Instead, either inset or impedance transformer is used to facilitate the 50‐Ω MS line feed. In this article, a simple MS line feed at the base is proposed using a single shorting post for impedance matching. By inserting a shorting post (via) closer to the edge of the base of an ETMSA, a wide range of impedances can be achieved at any of the edge by selecting proper shorting positions. A detailed investigation of an ETMSA with variation in shorting post position is carried out for the direct MS line feed. Experiments have been carried out to validate the concept.